A Logic Fuzzy Model for Evaluation of the Railway Station’s Practice Capacity in Safety Operating Conditions - Corriere F.; Vincenzo D. Di; Guerrieri M. (Archives of Civil Engineering, 2013)
The practice capacity of a railway junction depends, in addition to the effective operation’s conditions, by the potential risk factors related to the design plan of the railway station. With the aim of an approach based on the “fuzzy sets” it is possible to determine the numeric value of the practice capacity by the logic - qualitative relations between the features of the railway junction and the potential risk factors. This methodology permits to try out the absolute value of a suitable vector β, (less then the unit) for the utilization of the theoretic capacity in conditions of maximum reliability of the system related to the aspect of safety (technique “fail safe”).